The influence of labor and land use management on rice farming production in Pohuwato District - Syarwani Canon; Amir Halid; Fanny Daud (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The purposes of this research are: 1) to analyze the labor and land use area in Pohuwato District; 2) to analyze the effect of labor and land area usage on increased rice production in Pohuwato; 3) to analyze the factors of soil processing technology that have influence on rice production in Pohuwato District. The research method is survey method. The data analysis is descriptive analysis and multiple linear regression analysis. The results showed that the labor use in family and land are has a significant effect on rice production in Pohuwato District of Gorontalo. The other side that the technologies increase has no significant effect on rice production in Pohuwato District of Gorontalo. The results that showed insignificant effect because the technology has a good impact in increased production but not factual, so in the future it the need to evaluate in the technology adoption and the role of agricultural extension must be more optimal.